2D/2D Black Phosphorus/Nickel Hydroxide Heterostructures for Promoting Oxygen Evolution via Electronic Structure Modulation and Surface Reconstruction. Issue 25 (31st May 2022) - Mei, Jun; Shang, Jing; He, Tianwei; Qi, Dongchen; Kou, Liangzhi; Liao, Ting; Du, Aijun; Sun, Ziqi
Abstract: 2D heterostructures provide another exciting opportunity for extending the application of 2D materials in energy conversion and storage devices, due to their flexibility in electronic structure modulations and surface chemistry regulations. Herein, by coupling liquid‐exfoliated and mildly oxidized black phosphorus nanosheets (BP‐NSs) with wet‐chemically synthesized 2D nickel Ni(OH)2 nanosheets (NH‐NSs), 2D/2D heterostructured nanosheets (BNHNSs) are rationally constructed with a favorable transition of electron structure and desired intermediate adsorptions for alkaline oxygen evolution reaction (OER) catalysis. When used as an OER catalyst, to reach a current density of 10 mA cm −2, the overpotential of 2D/2D BNHNSs is only 297 mV, corresponding to a considerable decrease of 22% and 34% compared with the individual 2D NH‐NSs and 2D BP‐NSs, respectively. The structural tracking at the initial reconstruction stage via time‐dependent Raman spectra confirms that the phosphorus oxidization into the P–OH and the phase transformation into oxyhydroxide (NiOOH) significantly promote the electron transfer and electrocatalytic efficiency and thus endow the 2D/2D BNHNSs with much enhanced OER catalytic activity. This work offers new insights on the electron structure modulation of 2D‐based heterostructures and opens new avenues for regulating the adsorption of emerging phosphorene‐based materials for electrocatalysis. Abstract : To develop low‐cost nickel‐based electrocatalysts and broaden the application fields of the emerging black phosphorus, 2D/2D black phosphorus/Ni(OH)2 heterostructured nanosheets (BNHNSs) are rationally constructed for modulating electron structure and thus achieving desired intermediate adsorption behaviors in the alkaline oxygen evolution reaction, in which significantly enhanced catalytic activities with reduced overpotentials are achieved compared to each individual 2D unit.